Characterization of mutations in PRNP (prion) gene and their possible roles in neurodegenerative diseases - Bagyinszky E (Dove Medical Press, 2018)
Eva Bagyinszky,1 Vo Van Giau,1 Young Chul Youn,2 Seong Soo A An,1 SangYun Kim3 1Department of Bionano Technology, Gachon Bionano Research Institute, Gachon University, Gyeonggi-do, South Korea; 2Department of Neurology, Chung-Ang University College of Medicine, Seoul, South Korea; 3Department of Neurology, Seoul National University College of Medicine & Neurocognitive Behavior Center, Seoul National University Bundang Hospital, Seongnam, South Korea Abstract: Abnormal prion proteins are responsible for several fatal neurodegenerative diseases in humans and in animals, including Creutzfeldt–Jakob disease (CJD), Gerstmann–Sträussler–Scheinker disease, and fatal familial insomnia. Genetics is important in prion diseases, but in the most cases, cause of diseases remained unknown. Several mutations were found to be causative for prion disorders, and the effect of mutations may be heterogeneous. In addition, different prion mutations were suggested to play a possible role in additional phenotypes, such as Alzheimer’s type pathology, spongiform encephalopathy, or frontotemporal dementia. Pathogenic nature of several prion mutations remained unclear, such as M129V and E219K. These two polymorphic sites were suggested as either risk factors for different disorders, such as Alzheimer’s disease (AD), variant CJD, or protease-sensitive prionopathy, and they can also be disease-modifying factors. Pathological overlap may also be possible with AD or progressive dementia, and several patients with prion mutations were initially diagnosed with AD. This review also introduces briefly the diagnosis of prion diseases and the issues with their diagnosis. Since prion diseases have quite heterogeneous phenotypes, a complex analysis, a combination of genetic screening, cerebrospinal fluid biomarker analysis and imaging technologies could improve the early disease diagnosis. Keywords: genetics, mutation, prion, PRNP gene, Creutzfeldt–Jakob disease, Gerstmann–Sträussler–Scheinker disease, fatal familial insomnia, Alzheimer’s disease, diagnosis